#isolationfashion - Hinton, Casey and Layne (Ars Medica, 2022)
During the first Covid lockdown of 2020, Toronto artists and sisters Casey and Layne Hinton created a participatory art project to break up the monotony of pandemic isolation. They staged elaborate dress-up photo shoots using materials found within their living space, and invited viewers to do the same by following weekly styling prompts, including Tiger King and Retro Futurism. Viewers were invited to engage by sharing photos of their responses, and many did, to innovative and beautiful results.